2017
DOI: 10.1177/1747954117694922
|View full text |Cite
|
Sign up to set email alerts
|

System for notational analysis in small-sided soccer games

Abstract: The objective of this study was to compose an objective and detailed notational analysis system for 3 vs. 2 þ GK smallsided soccer games, in which three roles are examined: attacker with ball, attacker without ball and defender. The actions and the outcome of the actions were registered for each player and in each role. Players earn points for each action and outcome according to an a priori determined scheme. Performance scores for each role are calculated as the average number of points a participant earns p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…The in situ test was identical to the one described by Van Maarseveen, Oudejans, and Savelsbergh (in press) . The test comprised 3 versus 3 small-sided games (i.e., three attackers vs. two defenders and a goalkeeper) because these games are considered to comprise the basics of the game of soccer according to the Dutch Royal Soccer Association (KNVB; Dokter, 1993 ), and many more behavioural observations are possible in a given period of time when compared to an 11 versus 11 game ( Davids, Araújo, Correia, & Vilar, 2013 ).…”
Section: Experimental Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The in situ test was identical to the one described by Van Maarseveen, Oudejans, and Savelsbergh (in press) . The test comprised 3 versus 3 small-sided games (i.e., three attackers vs. two defenders and a goalkeeper) because these games are considered to comprise the basics of the game of soccer according to the Dutch Royal Soccer Association (KNVB; Dokter, 1993 ), and many more behavioural observations are possible in a given period of time when compared to an 11 versus 11 game ( Davids, Araújo, Correia, & Vilar, 2013 ).…”
Section: Experimental Studymentioning
confidence: 99%
“…The performance of the participants was assessed using the notational system designed by Van Maarseveen et al (in press) . In this system at any one point in time each player has one of three roles: attacker with ball, attacker without ball, and defender.…”
Section: Experimental Studymentioning
confidence: 99%
“…This makes it possible to obtain more accurate sport-specific performance predictions. Future research should take into account whether sport-specific performance measures, as demonstrated in the studies by van Maarseveen et al [12] and Fenner et al [13], accurately reflect sport-specific expertise, can function as the criterion, or have predictive value in the search for talented players.…”
mentioning
confidence: 99%
“…Quantifying performance as a continuous variable is already common for talent selection research in the fields of education and industrial-organizational psychology [10,11]. In the area of soccer, two interesting recent studies are those by van Maarseveen et al [12], who aimed to quantify soccer performance by means of a notational analysis, and the study by Fenner et al [13], who used a cumulative ranking point system. Both studies examined soccer performance that emerges in small-sided games, which also corresponds with Johnston et al's [1] plea for future studies to incorporate a more ecological design.…”
mentioning
confidence: 99%
“…With video analysis, both technical and tactical skills can be observed. Technical skills are mostly determined by quantifying (successful or direction of) actions on the ball (Hughes & Bartlett, 2002;Vilar, Araújo, Davids, & Button, 2012), where tactical skills are mostly related to qualitative observations of decision-making (van Maarseveen, Oudejans, & Savelsbergh, 2017). At this point it is important to note that soccer players are considered as the performers of the game .…”
mentioning
confidence: 99%